Analysis of the Mermule Tradition and Visit of Mbah Buyut Tambi, Tambi Village, Sliyeg District, Indramayu Regency - Didik Himmawan; Tri Ulfah Nurjanah (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
The Tomb of Mbah Buyut Tambi is a historical and religious site with unique and sacred traditions, such as "Unjungan" and "Mermule". These traditions are a form of respect for ancestors and a means of fostering friendship between residents. This tomb has several forbidden myths believed by the local community. This study aims to describe the traditions and beliefs that exist at the Tomb of Mbah Buyut Tambi and the importance of preserving this culture for future generations. By understanding and respecting the traditions and beliefs in this place, visitors can feel the true tranquility and sanctity of the place. The method used is participatory observation. Researchers directly dive into observing, interviewing, recording, and documenting data. Data collection techniques used are observation, interviews, and documentation, the appropriate informants for this study are the kuncen and community leaders of Tambi concerned. The data analysis technique in this study involves three components, namely the presentation of information from informants, information reduction, and drawing conclusions. The results of this study are, this tradition is not only a form of respect for ancestors, but also a means of fostering friendship and cultural preservation. This tomb is home to several myths and prohibitions believed by the local community. By understanding and respecting the traditions and beliefs of this site, visitors can experience the serenity and true sanctity of the place.